2006
DOI: 10.1002/ajim.20320
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function abnormalities and airway irritation symptoms of metal fumes exposure on automobile spot welders

Abstract: These findings suggest that restrictive and obstructive lung abnormalities, and airway irritation symptoms are associated with spot and arc welding exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…However, the decreased pulmonary function was only proportional to smoking in Plant 1. The association between welding exposure duration and decreased pulmonary function were in agreement with other investigation [5], [15]. Previous studies on welders also suggest a cumulative relation between the effects of smoking and welding, hence causing increase respiratory symptom and lung disease [8], [9], [11].…”
Section: Methodssupporting
confidence: 91%
“…However, the decreased pulmonary function was only proportional to smoking in Plant 1. The association between welding exposure duration and decreased pulmonary function were in agreement with other investigation [5], [15]. Previous studies on welders also suggest a cumulative relation between the effects of smoking and welding, hence causing increase respiratory symptom and lung disease [8], [9], [11].…”
Section: Methodssupporting
confidence: 91%
“…Reported adverse respiratory outcomes include metal fume fever [2], siderosis [3], lobar pneumonia [4] and less definitively, lung cancer [5,6] and asthma [7][8][9][10][11][12]. Although some studies have shown an increased prevalence of chronic bronchitis in welders [9], this finding is not universal [13].…”
Section: Introductionmentioning
confidence: 73%
“…Ni is a common component of alloy metals and is used in electroplating, stainless steel, coins, and jewelry (4,6,7). Inhalation of Ni has been associated with lung and nasal cancers (5,(8)(9)(10), fibrosis, and various other cardiopulmonary diseases (1,5), including acute lung injury (4,11).…”
mentioning
confidence: 99%
“…Nickel (Ni) is a well-known environmental and occupational hazard present in air pollution (1), cigarette smoke (2), diesel exhaust (3), and welding fumes (4,5). Ni is a common component of alloy metals and is used in electroplating, stainless steel, coins, and jewelry (4,6,7).…”
mentioning
confidence: 99%